An Understanding Emotion Representation in Lauv ft Lany Mean It: : Semantic Analysis - RIVIERA, TEQUIERO; Trihastuti, Nopita (Language Horizon: Journal of Language Studies, 2025)
ABSTRACT. The song ’Mean It’ by Lauv and Lany stands out as a work that combines emotional lyrics with melancholic melodies, creating a profound experience for listeners. This paper aims to analyze the lyrics of the song using semantic theory in linguistics and explore its impact on listeners’ emotions. Using a semantic approach, this research examines the literal meaning of words and phrases in the lyrics. The results show that the lyrics in ’Mean It’ imply feelings of insecurity, rejection and vulnerability, which reinforce emotional responses such as sadness and confusion in listeners. In addition, the viral phenomenon of this song on social media such as TikTok demonstrates how emotional musical content influences social interactions and creates emotional resonance among global audiences. This research contributes to a better understanding of the relationship between lyrics, semantics and emotions in popular music. Keywords: Lyrics; Songs; Emotion; Semantics; Popular Music